Safety and efficacy of perioperative benzodiazepine administration: study protocol for a systematic review and meta-analysis - Waleed Alhazzani; Jessica Spence; Emilie Belley-Cote; Richard Whitlock; Jack Young; Kevin Um; David Mazer; Chris Beaver; Eric Jacobsohn (BMJ Open)
Introduction Perioperative benzodiazepines are used because of their anxiolytic, sedative and amnestic effects. Evidence has demonstrated an association of benzodiazepines with adverse neuropsychiatric effects. Nonetheless, because of their potential benefits, perioperative benzodiazepines continue to be used routinely. We seek to evaluate the body of evidence of the risks and benefits of benzodiazepine use during the perioperative period.Methods and analysis We will search Cochrane CENTRAL, MEDLINE, EMBASE, PsychINFO, CINAHL and Web of Science from inception to March 2019 for randomised controlled trials (RCTs) and observational studies evaluating the administration of benzodiazepine medications as compared with all other medications (or nothing) in patients undergoing cardiac and non-cardiac surgery. We will exclude studies assessing the use of benzodiazepines for procedural sedation or day surgery. We will examine the impact of giving these medications before, during and after surgery. Outcomes of interest include the incidence of delirium, duration of delirium, postprocedure cognitive change, the incidence of intraoperative awareness, patient satisfaction/quality of life/quality of recovery, length-of-stay (LOS) in the intensive care unit (ICU), hospital LOS and in-hospital mortality.Reviewers will screen references and assess eligibility using predefined criteria independently and in duplicate. Two reviewers will independently collect data using prepiloted forms. We will present results separately for RCTs and observational studies. We will pool data using a random effect model and present results as relative risk with 95% CIs for dichotomous outcomes and mean difference with 95% CI for continuous outcomes. We will pool adjusted ORs for observational studies. We will assess risk of bias for individual studies using the Cochrane Collaboration tool for RCTs. For observational studies, we will use tools designed by the Clinical Advances through Research and Information Translation group. Quality of evidence for each outcome will be assessed using the Grading of Recommendations Assessment, Development and Evaluation approach.Ethics and dissemination This systematic review involves no patient contact and no interaction with healthcare providers or systems. As such, we did not seek ethics board approval. We will disseminate the findings of our systematic review through the presentation at peer-reviewed conferences and by seeking publication in a peer-reviewed journal.PROSPERO registration number CRD42019128144